2022
DOI: 10.3390/life12030432
|View full text |Cite
|
Sign up to set email alerts
|

Response of Circulating Inflammatory Markers to Intermittent Hypoxia-Hyperoxia Training in Healthy Elderly People and Patients with Mild Cognitive Impairment

Abstract: Intermittent hypoxia-hyperoxia training (IHHT) is a non-pharmacological therapeutic modality for management of some chronic- and age-related pathologies, such as Alzheimer’s disease (AD). Our previous studies demonstrated significant improvement of cognitive function after IHHT in the patients with mild cognitive impairment (MCI). The present study further investigated the effects of IHHT on pro-inflammatory factors in healthy elderly individuals and patients with early signs of AD. Twenty-nine subjects (13 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…However, in another study [ 36 ] included in this review, no change in C-reactive protein levels was observed after an 8-week intervention of passive hypoxia. Previous studies have suggested that IH protocols could exert an anti-inflammatory and tissue-protective effects [ 68 , 69 ], notably via the suppression of pro-inflammatory mediators such as TNF-α and IL-4 [ 70 ] and contribution to the production of anti-inflammatory interleukins by B cells [ 71 ]. However, when using active IH, such as resistance training with elastic bands during a 24-week intervention [ 34 ], no additive effect on inflammatory biomarkers was observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study [ 36 ] included in this review, no change in C-reactive protein levels was observed after an 8-week intervention of passive hypoxia. Previous studies have suggested that IH protocols could exert an anti-inflammatory and tissue-protective effects [ 68 , 69 ], notably via the suppression of pro-inflammatory mediators such as TNF-α and IL-4 [ 70 ] and contribution to the production of anti-inflammatory interleukins by B cells [ 71 ]. However, when using active IH, such as resistance training with elastic bands during a 24-week intervention [ 34 ], no additive effect on inflammatory biomarkers was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent hypoxia-hyperoxia (IHH) is a modified IH protocol. The normoxia period is replaced by a moderate hyperoxia period (FiO 2 = 30-40%), resulting in a faster recovery from deoxygenation (Bayer et al, 2017;Glazachev et al, 2017;Dudnik et al, 2018;Serebrovska et al, 2019cSerebrovska et al, , 2022Afina et al, 2021;Behrendt et al, 2022;Bestavashvili et al, 2022). Compared with IH, IHH offers a more obvious improvement in the clinical parameters and is considered to offer more beneficial effects (Serebrovska et al, 2019a).…”
Section: Different Forms Of Intermittent Hypoxia Conditioningmentioning
confidence: 99%
“…Serebrovska et al (2019c) showed that IHH conditioning can improve the cognitive function of patients with mild cognitive impairment and reduces the biomarkers for Alzheimer's disease in the peripheral blood while increasing the levels of some inflammatory markers. The upregulation of inflammatory markers may be a potential trigger for cellular adaptation (Serebrovska et al, 2022), but whether these proinflammatory factors mediate the neuroprotective effects is unclear and needs to be further explored.…”
Section: Hypoxia and Neurovascular Regenerationmentioning
confidence: 99%
“…In order to enhance the activity of transcription factors (e.g., nuclear factor kappa B, hypoxia induced factor 1α), which augments the expression of signalling proteins (e.g., VEGF, NOs, and PGC-1α) and thus the beneficial adaptive effects of the intermittent hypoxic stimulus, it is hypothesized that normoxic periods should be replaced by moderate hyperoxia (fraction of inspired oxygen [F i O 2 ] = 0.30–0.40, termed intermittent hypoxic-hyperoxic exposure [IHHE]) ( Sazontova et al, 2012 ; Mallet et al, 2020 ; Burtscher et al, 2022 ). Previous studies have shown that IHHE is safe and well-tolerated in various clinical populations such as patients with coronary artery disease ( Glazachev et al, 2017 ), ischemic heart disease ( Tuter et al, 2018 ), mild cognitive impairment ( Serebrovska et al, 2022 ), prediabetes ( Serebrovska et al, 2019 ), comorbidities ( Dudnik et al, 2018 ), and in geriatric patients ( Bayer et al, 2017b ; Behrendt et al, 2022a ). Hence, intermittent exposure to hypoxia and hyperoxia is expected to have beneficial effects on two of the most common age-related risk factors/comorbidities (i.e., hypertension and dyslipidemia) and is well applicable in geriatric patients.…”
Section: Introductionmentioning
confidence: 99%